2012
DOI: 10.1002/bjs.7799
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of omega-3 fatty acid-supplemented enteral nutrition versus standard enteral nutrition in patients undergoing oesophagogastric cancer surgery

Abstract: BackgroundOesophagogastric cancer surgery is immunosuppressive. This may be modulated by omega-3 fatty acids (O-3FAs). The aim of this study was to assess the effect of perioperative O-3FAs on clinical outcome and immune function after oesophagogastric cancer surgery.MethodsPatients undergoing subtotal oesophagectomy and total gastrectomy were recruited and allocated randomly to an O-3FA enteral immunoenhancing diet (IED) or standard enteral nutrition (SEN) for 7 days before and after surgery, or to postoperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
126
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 27 publications
2
126
3
Order By: Relevance
“…Moreover, partial preoperative EN support has been verified to facilitate the postoperative gastrointestinal absorption of nutrients by gastric cancer patients, accelerate the recovery of patients, and enhance the overall clinical outcome (15). It is also noted that previous study reported that nutrition support should be limited to gastric cancer patients who severely malnourished (16), the present study did not address in this regard.…”
Section: Ding Et Al Effects Of Preoperative and Postoperative Enteralmentioning
confidence: 72%
“…Moreover, partial preoperative EN support has been verified to facilitate the postoperative gastrointestinal absorption of nutrients by gastric cancer patients, accelerate the recovery of patients, and enhance the overall clinical outcome (15). It is also noted that previous study reported that nutrition support should be limited to gastric cancer patients who severely malnourished (16), the present study did not address in this regard.…”
Section: Ding Et Al Effects Of Preoperative and Postoperative Enteralmentioning
confidence: 72%
“…Several trials have evaluated the effects of different nutrients on the short-term outcomes following various types of gastrointestinal surgery. For example, some studies have shown that perioperative nutrient supplementation significantly reduces the incidence of postoperative complications and length of hospital stay [26,27], whereas others have failed to demonstrate any benefits from nutrient therapy [28,29]. Therefore, whether perioperative nutritional intervention in underweight patients with gastric cancer can improve their long-term outcome remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer patients show relatively severe malnutrition, as a result of many factors, including surgical trauma, perioperative diet control, and low calorie intake, as well as from factors related to gastric cancer itself (Sultan et al, 2012). It has been shown previously in studies on enteral nutrition (EN) in the surgical treatment of diseases that early EN plays an important role in postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%